Phytotherapy for leucorrhoea from Srikakulam district of Andhra Pradesh - and T.V.V. Seetharami Reddi, Ramarao Naidu, B.V.A., *J. Koteswara Rao (International Multidisciplinary Research Journal, 2011)
<div style="border-right: medium none; padding-right: 0in; border-top: windowtext 1pt solid; padding-left: 0in; padding-bottom: 0in; margin-left: 34pt; border-left: medium none; margin-right: 34pt; padding-top: 1pt; border-bottom: medium none; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> The present study yielded 29 empirically accepted and commonly used phytotherapeutical practices of 29 plant species from 29 genera belonging to 21 families with additives for curing leucorrhoea by the tribals and folklore of Srikakulam district. The mode of administration of drugs along with their dosage was studied.